2012
DOI: 10.1016/j.ejmg.2011.12.011
|View full text |Cite
|
Sign up to set email alerts
|

Array comparative genomic hybridization: Results from an adult population with drug-resistant epilepsy and co-morbidities

Abstract: BackgroundThe emergence of array comparative genomic hybridization (array CGH) as a diagnostic tool in molecular genetics has facilitated recognition of microdeletions and microduplications as risk factors for both generalised and focal epilepsies. Furthermore, there is evidence that some microdeletions/duplications, such as the 15q13.3 deletion predispose to a range of neuropsychiatric disorders, including intellectual disability (ID), autism, schizophrenia and epilepsy.We hypothesised that array CGH would re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 34 publications
0
23
0
Order By: Relevance
“…Thus, incomplete penetrance and a high phenotypic variability were assumed. Galizia et al (18) found a gain involving CHRNA7 in a patient with epilepsy and brain malformations, and they suggested that either the duplication or the structural change could be the 'second hit'. Likewise, the maternally inherited duplication 15q25.1 in patient 9 which affects the genes CHRNA3 and CHRNB4 may have an effect in the etiology of epilepsy, possibly in association with a second hit or a modifier.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, incomplete penetrance and a high phenotypic variability were assumed. Galizia et al (18) found a gain involving CHRNA7 in a patient with epilepsy and brain malformations, and they suggested that either the duplication or the structural change could be the 'second hit'. Likewise, the maternally inherited duplication 15q25.1 in patient 9 which affects the genes CHRNA3 and CHRNB4 may have an effect in the etiology of epilepsy, possibly in association with a second hit or a modifier.…”
Section: Discussionmentioning
confidence: 99%
“…Transmitting parents, with and without phenotypes, were included. In total, 90 individuals with duplications involving CHRNA7 were available for review [1,16,17,27,31,32,42,43,4649,53,5759]. …”
Section: Phenotypes Associated With Changes In Chrna7 Copy Numbermentioning
confidence: 99%
“…The most common duplications of CHRNA7 , with an estimated prevalence of one in 174 to one in 186 individuals, encompass only the gene itself or include the first exon of OTUD7A , with 67 cases identified in the literature for which clinical data are available [1,3,31,32,46,47,53,5759]. Of these, 53 (79.1%) have unknown inheritance (Figures 2 & 3).…”
Section: Phenotypes Associated With Changes In Chrna7 Copy Numbermentioning
confidence: 99%
“…If the physical examination does not reveal a recognizable syndrome, it is reasonable to proceed with array comparative genomic hybridization (CGH) to assess for copy number variations that may explain the phenotype [187]. Array CGH has been helpful in detecting chromosomal causes of epilepsy in 10–30% of patients with seizures [188190]. …”
Section: Work-up and Management Of Genetic Epileptic Encephalopathiesmentioning
confidence: 99%